The preparation and utilization of Calamansi fruit pulp (Citrus mitis blanco) - Tenmatay, Lourdes A.; De Leon, Sonia Y. (1965.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Citrus fruits -- Philippines